2022
DOI: 10.1002/adhm.202202205
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid‐Conjugated Nanoparticles Suppression of Platelet Activation and Disruption to Tumor Vascular Barriers for Enhancing Drug Penetration in Tumor

Abstract: Hypercoagulation threatens the lives of cancer patients and cancer progression. Platelet overactivation attributes to the tumor‐associated hypercoagulation and maintenance of the tumor endothelial integrity, leading to limited intratumoral perfusion of nanoagents into solid tumors in spite of the enhanced penetration and retention effect (EPR). Therefore, the clinical application of nanotherapeutics in solid cancer still faces great challenges. Herein, this work establishes platelet inhibiting nanoagents based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…As a result, the drugs exhibit more potent anti-tumor effects in the U14 tumor-bearing mice model. 70 Wang's team also prepared an 'ion/gas' bioactive nanogenerator (called IGBN) comprising a copper-based MOF and a loaded cisplatin-arginine (Pt-Arg) prodrug, which is a pH/GSH-responsive complex. The acidic pH in the tumor microenvironment breaks down the MOF, releasing Pt-Arg.…”
Section: Nanoparticles With Multiple Excitation Modesmentioning
confidence: 99%
“…As a result, the drugs exhibit more potent anti-tumor effects in the U14 tumor-bearing mice model. 70 Wang's team also prepared an 'ion/gas' bioactive nanogenerator (called IGBN) comprising a copper-based MOF and a loaded cisplatin-arginine (Pt-Arg) prodrug, which is a pH/GSH-responsive complex. The acidic pH in the tumor microenvironment breaks down the MOF, releasing Pt-Arg.…”
Section: Nanoparticles With Multiple Excitation Modesmentioning
confidence: 99%
“…HE-stained sections of the tumor tissue showed that PD/ Pep1 treatment led to a large region of apoptotic cells and had a significant killing effect on the tumor cells (Figure 6B and Figure S27). The distributions of the platelet marker CD41, 49 the surface marker of platelet activation P-selectin, 11,50 and the EMT-related indicators E-cadherin, N-cadherin, and vimentin in the tumor tissues in different treatment groups were detected by immunohistochemical staining of tissue sections. The level of E-cadherin in the PD/Pep1 group was significantly higher than that in the other groups, and the levels of vimentin and N-cadherin were lower than those in the other groups (Figure 6C 54 It was found that PD/Pep1 can inhibit tumor-associated platelets, which in turn reduces EMT in tumor cells, thereby ultimately demonstrating excellent antitumor effects.…”
Section: In Vivo Antitumor Effectsmentioning
confidence: 99%
“…7−9 However, platelets can maintain the integrity of the tumor vasculature, limiting the perfusion of nanoparticles into solid tumors. 10,11 Dipyridamole (DIP) is a platelet inhibitor used for the secondary prevention of a transient ischemic attack. DIP inhibits phosphodiesterase activity, preventing platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Recently, natural phenolic acids have drawn widespread attention by virtue of their multifarious biological and pharmacologic actions. [17][18][19][20][21][22] Choosing appropriate candidates to address dilemmas such as residual tumor cells and large bone defects after osteosarcoma resection is indeed a significant challenge. Chlorogenic acid (CA), a typical phenolic acid derived from various herbs, such as Flos Lonicerae Japonicae and Eucommia Ulmoides, not only exhibits antitumor ability but also shows osteoinductive effect.…”
Section: Introductionmentioning
confidence: 99%